Electron/ion-conductive and flexible dual-functional copolymer enabled by EDOT and h2PDMS for optimized Li-ion batteries - Jingwei Wang; Zhaowen Bai; Zejia Zhao; Guangping Zheng; Junye Cheng; Guohua Chen (Nano Research Energy)
Electron/ion-conductive flexible copolymer PEDOT-PDMS (poly(3,4-ethylenedioxythiophene)-poly(dimethylsiloxane)) was successfully developed, which not only effectively optimizes high-voltage NaLiFePO4F cathode through dripping on electrode surface but also improves high-capacity Si anode through in-situ polymerization on the surface of Si particles. Theoretical calculation and experiments indicate that π-π conjugated structure in PEDOT-PDMS molecular chains easily interacts with PF6– anions, providing electron transfer pathways and preventing HF production. Moreover, Li ions transfer through Si-O in the amorphous phase of the copolymer, and its Young’s modulus at rupture is 1.17±0.10 MPa. The in-situ TEM results directly confirm that the polymer layer provides conducting pathways and buffers the stress induced by lithiation. With the NaLiFePO4F coated cathode, the cells show good cycle stability (~100% of capacity retention after 500 cycles) and high chemical diffusion coefficient of lithium-ions (1.89×10–9 cm2·s–1 and 1.20×10–9 cm2·s–1). In the case of coated Si anode, a capacity of 1512 mAh·g–1 is retained after 1000 cycles at 0.5 C with a capacity retention of 69.8% in terms of the highest specific capacity around the 160th cycle. This work opens a new avenue for the simultaneous optimization of cathode and anode with a functional polymer.